2019
DOI: 10.1002/ejoc.201901164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isotopically Labelled Disparlure Enantiomers and Application to the Study of Enantiomer Discrimination in Gypsy Moth Pheromone‐Binding Proteins

Abstract: To study the binding mechanism of disparlure (7,8)‐epoxy‐2‐methyloctadecane enantiomers with pheromone‐binding proteins (PBPs) of the gypsy moth, oxygen‐17 or 18 and 5,5,6,6‐deuterium labelled disparlure enantiomers were prepared in an efficient, enantioselective route. Key steps involve the asymmetric α‐chlorination of dodecanal by SOMO catalysis and Mitsunobu inversion of a 1,2‐chlorohydrin. The pheromone, (+)‐disparlure (7R, 8S), was tested in two infested zones, demonstrating that it is very attractive tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Furthermore, the binding site residues that vary between LdisPBPs were found to be: Asn35, Ala73, Leu91, and Ala135 in LdisPBP1, whereas in LdisPBP2 these residues were substituted with Asp35, Thr73, Ile91 and Leu136 (Sanes and Plettner 2016). Our recent NMR and molecular docking studies have demonstrated that the disparlure enantiomers adopt different conformations and orientations in the binding pocket of LdisPBP1 and LdisPBP2 (Pinnelli et al 2019). In addition, the two PBPs differ in their ligand binding association and dissociation kinetics.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the binding site residues that vary between LdisPBPs were found to be: Asn35, Ala73, Leu91, and Ala135 in LdisPBP1, whereas in LdisPBP2 these residues were substituted with Asp35, Thr73, Ile91 and Leu136 (Sanes and Plettner 2016). Our recent NMR and molecular docking studies have demonstrated that the disparlure enantiomers adopt different conformations and orientations in the binding pocket of LdisPBP1 and LdisPBP2 (Pinnelli et al 2019). In addition, the two PBPs differ in their ligand binding association and dissociation kinetics.…”
Section: Introductionmentioning
confidence: 90%
“…The enantiopure α-chloroaldehyde 8 could be prepared from aldehyde intermediate 10 via asymmetric α-chlorination. We used the same approach to prepare (+)-and (-)-disparlure enantiomers (Pinnelli et al 2019). The asymmetric -chlorination of an aldehyde was also used previously in the synthesis of the posticlure enantiomers, which have a trans epoxide moiety (Kang and Britton 2007).…”
Section: Design Of 6-fam-tagged Disparlure Enantiomersmentioning
confidence: 99%
“…They include the use of naturally occurring chiral substrates, such as ʟ-glutamic acid [13], ʟ-tartaric acid [14][15][16], ᴅ-glucose [17], and sorbitol [18] as starting materials, as well as enantioselective reactions, such as the Sharpless epoxidation [19][20][21][22][23][24], asymmetric dihydroxylation [25,26], chloroallyloboronation [27], or iodolactonization [28]. Most recently a method using the asymmetric chlorination of dodecanal by LiCl in the presence of a chiral imidazolidinone catalyst has also been described [29]. However, many of these methods have some drawbacks -the most important one being the insufficient enantiomeric purity for biological and commercial applications [29].…”
Section: Synthesis Of Disparlure and Monachalure Enantiomers From 23mentioning
confidence: 99%
“…Most recently a method using the asymmetric chlorination of dodecanal by LiCl in the presence of a chiral imidazolidinone catalyst has also been described [29]. However, many of these methods have some drawbacks -the most important one being the insufficient enantiomeric purity for biological and commercial applications [29]. (+)-Disparlure used in most commercial lures is prepared by the Sharpless epoxidation reaction, which gives the final product with ees not exceeding 95% [29], which is insufficient to be used as attractant for males of the Gypsy moth.…”
Section: Synthesis Of Disparlure and Monachalure Enantiomers From 23mentioning
confidence: 99%
See 1 more Smart Citation